Applications of 3 Tesla CMR in acute coronary syndromes (ACS) - Dall'Armellina, E (2012)
Introduction: There is a pressing clinical need to treat patients with acute coronary syndrome (ACS) timely and efficiently in order to improve their prognosis. Standard tools available in ED, while useful, do not comprehensively characterize ACS for either diagnosis or risk stratification. The role of CMR in ACS is emerging because it allows assessment of both myocardial composition and function. Newer CMR techniques such as: a) T2 W imaging for assessing myocardial oedema and area at risk B) pre contrast T1 mapping techniques for quantitative characterization of the tissue composition, are adding further utility for CMR in ACS. At present the clinical use of these techniques is still limited and further investigations are needed to assess their clinical applicability in ACS patients. Aims: The aims of this thesis were several. Firstly we sought to establish a CMR protocol for imaging ACS patients on a 3T CMR scanner. In order to do so, we validated a novel T2 W technique for oedema imaging (T2 prep SSFP) at 3T. Second, we aimed to perform a detailed study of the time course of oedema in ACS patients in order to establish the appropriate imaging time for the assessment of area at risk. Third, by applying T2W acute oedema imaging, we sought to investigate the functional and pathological meaning of complicated remote plaques in patients with multivessel disease. Finally, we aimed to establish whether, in comparison to standard CMR techniques, novel precontrast T1 mapping allows better characterization of the acutely injured myocardium and whether it can predict long-term functional recovery. Methods: The research studies were all performed on a 3T Trio Siemens scanner. In the initial stage of the research, we validated the T2 W technique performing phantom work and scanning both volunteers and patients to assess the uniformity of signal intensity in the myocardium and to establish a threshold based method to post process the images. We then established a CMR protocol for ACS including oedema imaging, T1 mapping imaging, perfusion, functional and late gadolinium enhancement imaging. Patients with acute myocardial infarction (both ST elevation myocardial infarction (STEMI) and non STEMI) were scanned at 4 different time points after the acute event (3 scans within 2 weeks and one at 6 months). All STEMI patients underwent primary percutaneous coronary intervention (PCI) while the non-STEMI patients underwent coronary angiography and /or PCI. Results: We validated the T2prep SSFP technique at 3T, highlighting its limitations and establishing a threshold of mean ± 2SD to assess myocardial oedema. We found that the optimal imaging window to assess the maximal expression of myocardial oedema was within 1 week from the acute event in patients with ST elevation MI. Also, our results showed a reduction of LGE over time (from acute to chronic) in segments which also showed improvement in contractile function indicating that even segments with transmural LGE assessed in the early hours post event could be viable. By applying these techniques in acute patients with bystander disease undergoing percutaneous coronary intervention, we found that: 1) T2W imaging can detect myocardial injury downstream from a vessel identified as "non culprit" 2) in 20% of NSTEMI patients, the angiographic assessment alone failed to identify the culprit vessel. Finally, we found that the diagnostic performance of acute pre-contrast T1-mapping was at least as good as that of T2W CMR for detecting myocardial injury. There was a significant relationship between the segmental damaged fraction assessed by either by LGE or T2W, and mean segmental T1 values and the likelihood of improvement of segmental function at 6 months decreased progressively as acute T1 values increased. Conclusions: In summary, we defined a stable imaging window for the retrospective evaluation of area at risk and we also indicated that acutely detected LGE does not necessarily equate with irreversible injury and may severely underestimate salvaged myocardium. Furthermore, in NSTEMI patients with multivessel disease, by revealing acute myocardial damage in territories pertaining to vessels not treated acutely, we raised the issue of the need for better tools for the correct identification of the culprit vessel and to stratify patients rather than by angiographic assessment alone. Finally, we demonstrated how pre-contrast T1 mapping allows for assessment of the extent of myocardial damage and how T1 mapping might become an important complementary technique to LGE and T2W for the identification of reversible myocardial injury and the prediction of functional recovery in acute MI.